The Semiosphere, Between Informational Modernity and Ecological Postmodernity - Patoine, Pierre-Louis; Hope, Jonathan (Recherches sémiotiques / Semiotic Inquiry, 2015)
The notion of semiosphere is certainly one of Lotman’s most discussed ideas. In this essay, we propose to investigate its ecological and biological dimensions, tracing them back to Vernadsky’s concept of biosphere and to Lotman’s environmental vision of art articulated in his early work, The Structure of the Artistic Text. Our investigation reveals how the biosemiotic undercurrents in Lotmanian thought enable the emergence of a cyclical, homeostatic model of culture that counterbalances a Modernist vision of art as a force working for unquestioned linear progress.